Recent Publications (Quarterly Journal of Economics, 1938)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 52, Issue 2, February 1938, Pages 360–365, https://doi.org/10.1093/qje/52.2.360 Published: 01 February 1938